Immunogenic peptides putatively from intratumor microbes: Opportunities for colorectal cancer treatment - Xiangyu Guan; Fanyu Bu; Yunyun Fu; Haibo Zhang; Haitao Xiang; Xinle Chen; Tai Chen; Xiaojian Wu; Kui Wu; Longqi Liu; Xuan Dong (iScience)
Summary: Recent evidence has confirmed the presence of intratumor microbes, yet their impact on the immunopeptidome remains largely unexplored. Here we introduced an integrated strategy to identify the immunopeptidome originated from intratumor microbes. Analyzing 10 colorectal cancer (CRC) patients, we identified 154 putative microbe-derived human leukocyte antigen (HLA)-I ligands. Predominantly bacterial in origin, these peptides were notably abundant in Fusobacterium nucleatum, the most prevalent bacterium differentiating between normal and tumor tissues. We discovered 20 peptides originating from F. nucleatum, thirteen of which, including two peptides shared across multiple patients, were tumor specific. Validation experiments confirmed that the putative microbe-derived peptide could activate CD8+ T cell responses. Our findings indicate that HLA-I molecules are capable of presenting intratumor microbe-derived peptides in CRC, potentially contributing to CD8+ T cell-mediated immunity and suggesting potential strategies for cancer immunotherapy.